Studi Kritik Hadis tentang Toleransi Beragama - Wiwin Widiawati; Rifki Rosyad; M Yusuf Wibisono (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about tolerance. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about tolerance in Muslim history No. 4773. The results and discussion of this study indicate that the status of the hadith regarding tolerance has the quality of hasan li ghairihi with maqbul ma'mul bih qualifications for the practice of Islam in the form of intimacy, not hostility and disputes between religious communities. This study concludes that the hadith narrated by Muslim No. 4773 is relevant to be used as the basis for the actualization of religious tolerance in Indonesia.